Library and library professional in the digital age / Nur Afeqah Abdullah and Nur Syafiqah Hassan - Abdullah, Nur Afeqah; Hassan, Nur Syafiqah (Universiti Teknologi MARA, 2021)
The purpose of this paper is to explore the future vision of library and librarians in the new technology demand referring new user needs, new skills for staff and services offered. This paper applies qualitative analysis in which the secondary research approach is used in collecting the existing data in the form of texts such research paper, journal, magazine and etc. to further explains about the topic. The literature reveals that transformation of new technologies giving an implication towards library staff, library services and future user demands. It also shows that communities are still relying on libraries for a variety of services and activities. Hence, the needs for librarians to manage libraries and help users to search information are still relevant. The deliberations in this paper are encircled by perception of what the library products, services, facilities and librarians' profession will be in future libraries. Further studies are needed to investigate the opportunities and possibility for professional librarians and library to enhance their roles facing new era IR 4.0.